Empowerment of Posyandu Cadres in Tuguraja Village with Digitalization and Creative Health Innovations - Shinta Siti Sundari; Evi Dewi Sri Mulyani; Teuku Mufizar; Ayu Rahmawati; Agus Supriatman; Rudi Hartono; Cepi Rahmat Hidayat; Dede Syahrul Anwar (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
One type of community-based health initiative that are planed and organized from, by, for and with the community is called Posyandu. The involvement of cadres is also essential to the success of Posyandu operations, they are responsible for establishing a connection between the community and health professionals or specialist  and helping to assisting and identify health needs. Cadres are also required to be able to provide information for health institutions that may not be able to reach the community directly, especially regarding Toddlers and the Elderly. With the development of technology towards digital, where the data management process is already based on Information Systems, it can provide ideas for cadres to use information systems as a tool to help their activity processes. The problems faced by cadres today are the lack of understanding regarding the use of digitalization as a medium for managing data and how to operate and maintain it. Meanwhile, in its current development, all stakeholders involved with Posyandu are already using the application. so we want to provide direct training regarding application use and maintenance, by conducting interviews and observations first . The results of the activities that have been carried out obtained results that with socialization and training regarding the importance of innovation with digitalization in posyandu services, they were able to understand and implement what was conveyed by the PKM team and could be realized optimally